The magic staff: a comprehensive overview of baculovirus-based technologies applied to human and animal health - Pidre, Matías Luis (2022)
Baculoviruses are enveloped, insect-specific viruses with large double-stranded DNA genomes. Among all the baculovirus species, Autographa californica multiple nucleopolyhedrovirus (AcMNPV) is the most studied. Due to its characteristics regarding biosafety, narrow host range and the availability of different platforms for modifying its genome, AcMNPV has become a powerful biotechnological tool. In this review, we will address the most widespread technological applications of baculoviruses. We will begin by summarizing their natural cycle both in larvae and in cell culture and how it can be exploited. Secondly, we will explore the different baculovirus-based protein expression systems (BEVS) and their multiple applications in the pharmaceutical and biotechnological industry. We will focus particularly on the production of vaccines, many of which are either currently commercialized or in advanced stages of development (e.g., Novavax, COVID-19 vaccine). In addition, recombinant baculoviruses can be used as efficient gene transduction and protein expression vectors in vertebrate cells (e.g., BacMam). Finally, we will extensively describe various gene therapy strategies based on baculoviruses applied to the treatment of different diseases. The main objective of this work is to provide an extensive up-to-date summary of the different biotechnological applications of baculoviruses, emphasizing the genetic modification strategies used in each field.